The Utilisation of Information Technology in Increasing Reading Interest in the Library of Sekolah Tinggi Teologi Imanuel (SETITEL) Telukdalam - Sunyianto, Sunyianto; Zakiah, Diana Mulida; Dao, Ose; Kerisman, Kerisman (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to determine the utilisation of information technology in increasing reading interest in the Library of Imanuel College (SETITEL) Telukdalam. The research method used is qualitative research. Data were collected using triangulation techniques, namely observation, interviews and documentation. Furthermore, the informants in this study were students of the Imanuel Theological College (SETITEL) Telukdalam with the characteristics of informants, namely 4th semester, 6th semester and 8th semester students totalling 6 people. The technique of taking informants using purposive sampling technique. The results of this study indicate that with the use of information technology in the Library of